he bad medicinal administration of analgesics and anti-inflammatory in elderly - Santos, Letícia Felix dos; Silva, Aline Santana da; Borin, Fabiane Yuri Yamacita (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
Aging predisposes the exacerbated consumption of drugs by elderly patients, whether prescribed or not, and this is due to the various physiological and metabolic changes related to aging, such as changes in body composition and reduced renal and liver functions. In addition, there is a change in the pharmacokinetics and pharmacodynamics of some drugs in the body of the elderly, which makes these patients susceptible to more intense adverse or therapeutic effects. Painkillers and anti-inflammatory drugs are widely consumed by the population as a whole, since they demonstrate efficacy and have free access for purchase and consumption, however they are highly dangerous for the body of the elderly who are no longer in better metabolic conditions. In view of this, this article will portray the metabolism of the elderly, what is the correct drug therapy to be indicated to them, demonstrate what changes in the functional parameters of the geriatric organism and what damage is caused by the uncontrolled consumption of painkillers and anti- inflammatory drugs, in addition to explaining the main strategies to promote the correct administration of medications and thus mitigate the health risks of these patients.